Low-Dose Ketamine Infusion as Adjuvant Therapy during an Acute Pain Crisis in Pediatric Patients. (10th January 2021) - Li, Cecilia; Doellner, Courtney; Leis, Aleda; Marinkovic, Annette; Gibbons, Kathleen; Wagner, Deborah
Abstract: Recent studies in pediatric patients have suggested that ketamine, an N-methyl-D-aspartate receptor (NMDA) antagonist, given at sub-anesthetic doses can effectively decrease pain scores, provide analgesic effects, and in some cases, reduce opioid requirements. Our study aims to assess impact of low-dose ketamine on reducing pain scores and total opioid requirements during an acute pain crisis in pediatric patients. From November 2016 to December 2018, eight patients between the ages of 2 and 17 years admitted to the pediatric intensive care unit (PICU) were treated with LDK infusions to manage severe, opioid-refractory, acute pain crises. Subjective pain scores and total morphine milligram equivalent (MME) intake before, during, and after ketamine infusion were collected through a structured chart review. Overall, the addition of ketamine appeared to reduce subjective pain scores and opioid requirements. Two patients were in palliative care and expired shortly after ketamine was started and two patients were discharged within 48 hours of LDK infusion cessation. Ketamine seemed to reduce heart rate and had no appreciable effect on respiratory rate, blood pressure, or oxygen saturation. Hallucination was reported in one patient which resolved upon dose reduction. LDK infusion could be considered as an adjuvant therapy to optimize pain control in pediatric patients experiencing acute pain crises. Further investigation with a larger patient population is warranted to establish the effects of LDK on pain improvement and reducing total opioid requirements.